THE CHANGING ROLE OF THE COURT INTERPRETER-TRANSLATOR IN AFRICA: THE CASE OF ZAMBIA - KASONDE, Alex (Comparative Legilinguistics, 2017)
The paper gives a historical account of the negative effects of poor interpreter-translator service providers to the development of the justice system in countries of Africa generally and Zambia in particular. It recommends various practical solutions to the challenge of access to interpreter-translator service providers generally and legal interpreter-translator services in particular. These include definition of target group; mobilization of funding; building a network of experts to serve as advisors, consultants and resource persons; establishment of a statutory body to guide government on language policy generally, including translation-interpretation services (e.g. Translation and Interpretation Commission); organization of thematic seminars and workshops; media panel discussions; moving a private motion in parliament; curriculum review for consideration by Ministry of Education; and submission of a draft bill for consideration by parliament and/or Ministry of Justice.